A Global Pact for the Environment: Conceptual foundations. Issue 1 (14th February 2019) - Aguila, Yann; Viñuales, Jorge E.
Abstract : This article introduces the conceptual foundations of the initiative towards the adoption of a Global Pact for the Environment. It first situates the search for a global framework instrument on environmental protection in a long‐term perspective and then discusses the main reasons why it is needed. Against this background, the article presents the current expression of this much broader trend, in the form of the initiative for a Global Pact for the Environment and the momentum it has generated in policy circles, first and foremost at the level of the United Nations General Assembly.